Clinical Results of Adjustable Sliding Hip Screw for Intertrochanteric Fracture of Femur - Morisawa, Keizo; Ichihara, Atsuyoshi; Harada, Masataka; Segata, Tateki (Orthopedics & Traumatology, 2002)
we treated intertrochanteric fractures of the femur by using adjustable sliding hip screw, and evaluated the clinical results. The mean age at the time of surgery was 79.4 years (range, 56 to 96 years). The mean duration of follow-up was 6.3 months (range, 1.5 to 14 months). X-ray showed that the mean angle of lag screw/plate was 130.3 degrees. The benefit of using adjustable sliding hip screw was variability (inserting point of guide pin, angle of lag screw fixation). All of the cases recovered well without varus deformity of the femoral neck and cutting out of the lag screw. One of them felt out of place in an area in which we inserted a plate at the time of final examination. The adjustable sliding hip screw system is useful for the treatment of intertrochanteric fracture of the femur.